Meteorological conditions for growing promising grape cultivars in the Black Sea agroecological zone of viticulture - V. S. Petrov; A. A. Marmorshtein; M. I. Pankin; D. M. Tsiku; M. D. Larkina (Труды по прикладной ботанике, генетике и селекции)
Background. The pattern and duration of the grape plant growing season depends both on biological characteristics of plants and the environmental conditions of their habitat. Studying meteorological conditions and their effect on the growing phases of grape cultivars of different origin is important to optimize the deployment of these cultivars.Materials and methods. Eight introduced and domestic grape cultivars served as the research material. Phenological observations were carried out according to M. A. Lazarevsky, ANOVA was performed according to B. A. Dospekhov, the dependence of the duration of growing phases on weather conditions was assessed using pairwise correlations, and Student’s t-test was applied to determine statistical significance. Meteorological data were taken from the agrometeorological bulletins for Krasnodar Territory. The studies were conducted in the period from 2018 to 2021 under the agroecological conditions of the Black Sea viticulture zone.Results. Specific features of the temperature regime for grape growing phases in the environments of the Black Sea viticulture zone were ascertained. Indicators of heat supply and duration of the growing season according to Lazarevsky were used to identify the studied cultivars as early (‘Podarok Dmitriya’, ‘Reliance’, ‘Brigantina’ and ‘Anapskiy Ranniy’), medium (‘Concord’ and ‘Venus’), mid-late (‘Prikubanskiy’), and late (‘Kyoho’) genotypes. The sum of active temperatures required for the growing season of early cultivars was 2522–2603°C, for medium ones 2755–2760°C, for mid-late ones 2835°C, and for late ones 2970°C. According to the international classification, ‘Podarok Dmitriya’, ‘Reliance’, ‘Brigantina’ and ‘Anapskiy Ranniy’ are early, ‘Concord’, ‘Venus’ and ‘Prikubanskiy’ are mid-early, and ‘Kyoho’ is medium-ripening. All cultivars had a close direct relationship between the duration of their growing phases and the sum of air temperatures above +10°C.